Study on root resorption after camouflage treatment of adult skeletal Class Ⅲ malocclusion with clear aligner - XIONG Zaidao, ZHANG Yanping, GU Yongchun, ZHOU Zhihao (Editorial Office of Stomatology, 2024)
Objective To compare the root resorption of posterior teeth between fixed orthodontic appliances and clear aligners in adult patients with skeletal Class Ⅲ malocclusion undergoing camouflage treatment by using cone-beam computed tomography(CBCT) measurements. Methods Thirty-two cases of skeletal Class Ⅲ malocclusion patients who had previously undergone camouflage treatment were retrospectively selected. Based on the type of orthodontic appliance used, they were divided into two groups (the fixed appliance group and the clear aligner group), each comprising 16 cases. CBCT images of the entire dental arch before and after treatment were collected for these patients, and three-dimensional reconstructions of the mandibular central incisors, first premolars, and first molars were generated using Mimics software. Changes in root volume and length of mandibular teeth before and after treatment were measured and compared between the two groups. Results Both groups showed significant reductions in measured root volume of the teeth after orthodontic treatment(P<0.05). In the clear aligner group, the mean reduction in root length of mandibular central incisors was (0.52±0.60)mm, while in the fixed appliance group, the reduction in root length of mandibular central incisors and first premolars was (0.47±0.38)mm and (0.38±0.25)mm, respectively. These differences were statistically significant(P<0.05). Except for the significantly lower reduction in root volume of mandibular central incisors in the clear aligner group compared to the fixed appliance group(P<0.05), there were no statistically significant differences in other root resorption-related parameters between the two groups(P>0.05). Conclusion In camouflage treatment of adult skeletal Class Ⅲ malocclusion patients, clear aligners can reduce the amount of root resorption in mandibular anterior teeth to a certain extent compared to fixed orthodontic appliances. However, there is no significant difference between the two appliances in the posterior teeth region.